Selection of fungal isolates for virulence against three aphid pest species of crucifers and okra - Bayissa, W.; Ekesi, S.; Mohamed, S.A.; Kaaya, G.P.; Wagacha, J.M.; Hanna, R.; Maniania, N.K. (Springer, 2017)
Aphids are regarded as important pest problems of vegetable crops worldwide. Most vegetable growers in sub-Saharan Africa heavily rely on synthetic chemical insecticides for aphids’ control. Fungus-based biopesticides are being considered as alternatives to chemical insecticides. This study evaluates virulence of five isolates of Metarhizium anisopliae and three of Beauveria bassiana against Brevicoryne brassicae, Lipaphis pseudobrassicae, and Aphis gossypii, and their thermotolerance and conidial yield as a prerequisite for strain selection. The study also evaluates performance of the best isolate in screenhouse experiment against target aphid species. Three isolates of M. anisopliae ICIPE30, ICIPE62, and ICIPE69 outperformed the others, causing mortality of 85–98 %, 83–97 %, and 73–77 %, in B. brassicae, L. pseudobrassicae, and A. gossypii, respectively, 7 days post-inoculation. Isolate ICIPE62 had the shortest LT50 values of 3.4, 2.5, and 2.6 days at 1 × 108 conidia ml−1, and the lowest LC50 values of 7.3 × 105, 9.3 × 104, and 3.0 × 104 conidia ml−1 on day 7 against A. gossypii, B. brassicae, and L. pseudobrassicae, respectively. Furthermore, ICIPE62 produced more conidia on the surface of aphid cadavers than ICIPE30 and ICIPE69 and showed wider thermotolerance with optimum ranges between 25 and 30 °C. Application of conidia of ICIPE62 formulated in aqueous and emulsifiable formulations negatively affected aphid population growth rate on kale and okra plants compared to controls in screenhouse experiments. These results have demonstrated the potential of M. anisopliae isolate ICIPE62 in suppression of A. gossypii, B. brassicae, and L. pseudobrassicae populations and could therefore be considered as biopesticide candidate for the control of these target aphids.